Photoaffinity probes for nematode pheromone receptor identification. Issue 1 (29th November 2019) - Zhang, Ying K.; Reilly, Douglas K.; Yu, Jingfang; Srinivasan, Jagan; Schroeder, Frank C.
Abstract : Identification of pheromone receptors plays a central role for uncovering signaling pathways that underlie chemical communication in animals. Abstract : Identification of pheromone receptors plays a central role for uncovering signaling pathways that underlie chemical communication in animals. Here, we describe the synthesis and bioactivity of photoaffinity probes for the ascaroside ascr#8, a sex-pheromone of the model nematode, Caenorhabditis elegans . Structure–activity studies guided incorporation of alkyne- and diazirine-moieties and revealed that addition of functionality in the sidechain of ascr#8 was well tolerated, whereas modifications to the ascarylose moiety resulted in loss of biological activity. Our study will guide future probe design and provides a basis for pheromone receptor identification via photoaffinity labeling in C. elegans .